The Costa Rican Identitarian Mirror in Dominican Land - Bustos Mora, Giselle (2018)
The gaze towards others has always been determined by the lenses inserted by social discourses. Based on the opinions of nationals and immigrants working or living in the Dominican Land, a sector of San José city, the article wants to show the role that certain discourses and social categories play in the possibilities of cultural interaction between groups of diverse origins. It brings into dialogue several identitarian constructions, such as gender, national identity and otherness, to identify several possibilities of intercultural encounters and dis-encounters surmised in this space. This approach departs from the perspective of cultural studies; for this, diverse tools of exploration and analysis have been applied, such as the narrative interview, observation, and Atlas Ti.